Medial swivel dislocation with impacted navicular bone into the talar head: A case report - Ibrahim Saeed Ibrahim; Isam Sami Moghamis; Kareem Elsweify; Jasim Alsaei; Ahmad AL-Saddi; Mazhar Fuad (Trauma Case Reports)
Medial swivel dislocation is a rare subtype of midtarsal bone dislocation, mostly associated with fracture rather than isolated dislocation. It is caused by medially or laterally direct forces to the midfoot. In case of failed closed reduction of the deformity, the patient should undergo open reduction and stabilization of the injury as soon as possible. We are presenting a 17-year-old, male, who sustained a left ankle injury and presented with a deformity, closed reduction of the deformity failed multiple times, and the patient was taken for open reduction and stabilization of the deformity in the operating theater. Intra-operatively, the dislocation was locked with the lateral process of the navicular being impacted into the taller head. Six months following the injury the patient was back to his pre-injury status and did not have any recurrent dislocation of the midfoot.